Social Comparisons of Wage Increases and Job Satisfaction - Christian Grund; Maike Rubin (Institute for the Study of Labor (IZA), 2016)
We combine status quo and social comparison considerations and investigate whether relative wage increases in the sense of differences between individual wage increases and wage increases of comparable employees are related to managers' job satisfaction. Using a panel data set of managers in the German chemical industry, we indeed find first evidence. The relation between relative wage increases and job satisfaction is relevant for managers with lower absolute wage levels in particular.
Keywords: M52; J28; J31; 330; job satisfaction; reference points; social comparisons; status quo preferences; wage increases